A human whole-blood model to study the activation of innate immunity system triggered by nanoparticles as a demonstrator for toxicity - Ekdahl, Kristina N (Sci Technol Adv Mater, 2019)
In this review article, we focus on activation of the soluble components of the innate immune system triggered by nonbiological compounds and stress variances in activation due to the difference in size between nanoparticles (NPs) and larger particles or bulk material of the same chemical and physical composition. We then discuss the impact of the so-called protein corona which is formed on the surface of NPs when they come in contact with blood or other body fluids. For example, NPs which bind inert proteins, proteins which are prone to activate the contact system (e.g., factor XII), which may lead to clotting and fibrin formation or the complement system (e.g., IgG or C3), which may result in inflammation and vascular damage. Furthermore, we describe a whole blood model which we have developed to monitor activation and interaction between different components of innate immunity: blood protein cascade systems, platelets, leukocytes, cytokine generation, which are induced by NPs. Finally, we describe our own studies on innate immunity system activation induced by three fundamentally different species of NPs (two types of engineered NPs and diesel NPs) as demonstrator of the utility of an initial determination of the composition of the protein corona formed on NPs exposed to ethylenediaminetetraacetic acid (EDTA) plasma and subsequent analysis in our whole blood model.